The Effect of Problem Based Laboratory Activities on Self-Confidence, Self-Efficacy and Science Process Skills of Students - (:unkn) unknown (HACETTEPE UNIV, 2013)
In this study, it is aimed to establish whether or not that students of Science Education get involved in problem based laboratory activities on each experiment has an effect on their science process skills, their self-confidence and self-efficacy regarding biology laboratory. Study has been patterned at General Biology Laboratory 1 in accord with the model of pre-test post-test with control group with the students at second class of Science Education. While problem based laboratory activities are applied in experiment groups, traditional methods were used in control groups. SPST, self-confidence and self-efficacy tests regarding biology laboratory that were used in the study have been practised before and after practising. In addition, experiment group's students were asked to prepare experiment report and semi-structured interviews have been had with nine students. The data that obtained from scales, interviews and reports have been assessed as qualitative and quantitative. According to study's findings, while there is a significant difference between the post-test scores of students of experiment and control groups, there is not a difference found at their self-confidence and self-efficacy.
Keywords: science teaching; science process skills; problem based laboratory activities; self-confidence; self-efficacy